Survey Manajemen Kesehatan Ternak Ruminansia di Binjai, Sumatera Utara - Dewi, Rita Rosmala; Sihombing, Juli Mutiara; Ma’arif, Ikhwan (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2024)
Dewi, R.R, Sihombing, J.M., & Ma’arif, I. (2024). A Survey of health manajemen practices on livestock farm located in Binjai, North Sumatra. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-12 Tahun 2024, Palembang 21 Oktober 2024. (pp. 69–75). Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Practicing good health management in livestock is critical in controlling infectious diseases in livestock. This study attempts to evaluate the health management practices implemented by ruminant farmers in Binjai, North Sumatra. The study aimed to was carried out utilizing a survey method combined with interview techniques and field observations. This study included 56 ruminant farmers who raised cattle (37; 66.1%), goats (14; 25%), and sheep (5; 8.9%). The findings of this study revealed that approximately 68% of farmers have implemented sanitation and disinfection on their farms, whereas only a small percentage of farmers have received animal health training (8.9%), and there is little veterinary support in dealing with disease (16.1%). In treating their animals, farmers use anthelmintic drugs about 26.8% and the majority of farmers prefer antibiotics (42.9%) to herbs (7.1%) There is no significance difference between farmers' knowledge about health and sanitation application, veterinarian supports and drugs application among farmers. The majority of Binjai farmers have implemented farm sanitation measures. However, most farmers who have inadequate knowledge of livestock health have no support from veterinarians in diagnosing and treating the diseases. This possibly leads to inappropriate use of drugs by farmers. Farmers in Binjai should receive training regarding livestock health management to elevate a sustainable livestock productivity.